2021
DOI: 10.1093/jncics/pkab023
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Prostate Cancer Outcomes in Obese and Nonobese Men After Radical Prostatectomy

Abstract: Background The link between diabetes and prostate cancer progression is poorly understood and complicated by obesity. We investigated associations between diabetes and prostate cancer-specific mortality (PCSM), castrate-resistant prostate cancer (CRPC), and metastases in obese and nonobese men undergoing radical prostatectomy (RP). Methods We included 4,688 men from SEARCH, a cohort of men undergoing RP from 1988 to 2017. Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…27 Moreover, obesity is a risk factor for diabetes, and our group recently observed obesity-related differences in the associations between diabetes and PC outcomes. 28 If we consider that PR has the highest self-reported prevalence of DM among all states and territories, 29 it is plausible that both higher rates of diabetes and obesity may contribute to the worse PC mortality in PR, although this requires formal testing. Altogether, the complex interplay between biology, exposures, and social factors has not yet been elucidated and needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…27 Moreover, obesity is a risk factor for diabetes, and our group recently observed obesity-related differences in the associations between diabetes and PC outcomes. 28 If we consider that PR has the highest self-reported prevalence of DM among all states and territories, 29 it is plausible that both higher rates of diabetes and obesity may contribute to the worse PC mortality in PR, although this requires formal testing. Altogether, the complex interplay between biology, exposures, and social factors has not yet been elucidated and needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Kelkar and colleagues investigated the association between diabetes and prostate cancer-specific mortality. They found that diabetes was associated with increased risks of prostate cancer progression and mortality among obese men [ 51 ]. Similarly, Wu and colleagues reported that long-term plasma glucose fluctuation was significantly associated with the risk of cancer mortality (HR: 1.41 (95% CI: 1.04 - 1.92)), especially in the highest quartile of coefficient of variation of plasma glucose [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of association between DM and PCa is still insufficient. Moreover, obesity makes its pathophysiology a more complex situation[ 48 ].…”
Section: Prostate Cancer and Diabetes Linco1128mentioning
confidence: 99%